2012
DOI: 10.1007/s00284-012-0094-7
|View full text |Cite
|
Sign up to set email alerts
|

Ciprofloxacin-Induced Antibacterial Activity is Reversed by Vitamin E and Vitamin C

Abstract: In the present study, we investigated the possible involvement of oxidative stress in ciprofloxacin-induced cytotoxicity against several reference bacteria including Pseudomonas aeruginosa ATCC 27853, Escherichia coli ATCC 25922, Staphylococcus aureus ATCC 29213, and clinical isolate of methicillin-resistant Staphylococcus aureus (MRSA). Oxidative stress was assessed by measurement of hydrogen peroxide generation using a FACScan flow cytometer. The antibacterial activity of ciprofloxacin was assessed using the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
33
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 23 publications
(38 citation statements)
references
References 27 publications
4
33
1
Order By: Relevance
“…In agreement, ciprofloxacin susceptibility of these bacterial strains was previously shown [17,24,25]. Additionally, reactive oxygen species had essential role in the antibacterial effect of ciprofloxacin against bacteria such as P.…”
Section: Discussionsupporting
confidence: 68%
See 4 more Smart Citations
“…In agreement, ciprofloxacin susceptibility of these bacterial strains was previously shown [17,24,25]. Additionally, reactive oxygen species had essential role in the antibacterial effect of ciprofloxacin against bacteria such as P.…”
Section: Discussionsupporting
confidence: 68%
“…We have recently shown that vorinostat induce oxidative chromosomal damage leading its mutagenic effect in blood lymphocytes [19]. Given the importance of reactive oxygen species, energy metabolism, mitochondrial functions for the antibacterial action of floroquinolones [5][6][7]17], it is probable that these mechanisms has a role in the observed enhancement of ciprofloxacin antibacterial activity by vorinostat. Thus, a drug-drug interaction between vorinostat and ciprofloxacin is a possibility.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations